Cyber Harassment Against Women Journalists in Indonesia: A Feminist Legal Perspective - Riczki Achmad Bahtiar; Ekky Agustin (The Indonesian Journal of Feminist Legal Studies, 2026)
The increasing use of digital platforms has transformed journalism while simultaneously exposing women journalists to various forms of cyber harassment. In Indonesia, online abuse directed at women journalists constitutes a growing threat to freedom of expression, professional safety, and gender equality. This article examines the nature of cyber harassment against women journalists and evaluates the adequacy of Indonesia’s legal framework in addressing such violations. Employing a feminist legal approach, the study analyzes legislation, policy instruments, documented cases, and relevant academic literature concerning online gender-based violence. The findings indicate that women journalists frequently experience gendered attacks, including sexualized threats, intimidation, doxxing, and coordinated online harassment campaigns. These practices not only affect individual well-being but also undermine media independence and democratic participation. Although Indonesia possesses several legal instruments that may be applied to cyber harassment cases, enforcement remains inconsistent and often fails to adequately recognize the gendered dimensions of online violence. The study further reveals that institutional responses frequently prioritize technical or criminal aspects while neglecting the structural inequalities that facilitate digital abuse. A feminist legal analysis demonstrates the necessity of integrating gender-sensitive approaches into legal interpretation, law enforcement practices, and digital governance frameworks. The article concludes that stronger legal protections, enhanced reporting mechanisms, and coordinated institutional responses are essential for safeguarding women journalists in digital environments. The findings contribute to broader discussions on digital rights, media freedom, and gender justice in contemporary democracies.